178-Nucleotide sequence surrounding the cos site of bacteriophage lambda DNA. - Nichols, B P (1978)
A nucleotide sequence of 61 nucleotides at the left end and 117 nucleotides at the right end of DNA from bacteriophage lambdacI857Sam7 was determined by the Maxam and Gilbert method. A perfect inverted repeat sequence of 10 nucleotides is near the left end, and one of 15 nucleotides is near the right end. DNA from another closely related lambda strain, lambdacI857prm116Sam7, has about 10% divergence in the sequence of the first 110 nucleotides at the right end and has a 17-member perfect inverted repeat sequence.